Ke Human Resource Management in Greenhouse Hydroponic Businesses - Prayuda, I Putu Putra Wardana; Budi Susrusa, Ketut; Korri Arisena, Gede Mekse; Bakhtiar, Ary (SOCA: Jurnal Sosial Ekonomi Pertanian, 2024)
Malang Raya is one of the vegetable-producing areas in East Java leading to many latest innovations related to vegetable cultivation, such as the hydroponic greenhouse system. This study aims to determine human resource management in hydroponic greenhouse farming in the Malang Raya area through business characteristics, work types, company organizational structure, human resource management functions, payroll and bonuses, and labor allocation.  This research used qualitative research methods that were processed by data reduction using Excel with data collected from 15 managers and actors of hydroponic greenhouse farms located in the Malang Raya area.  Meanwhile, the data processing method was descriptive quantitative and descriptive qualitative analysis.  The results of this study showed that most hydroponic farmers in the Malang Raya area use the NFT system with 2 different greenhouse models, namely open greenhouses and closed greenhouses. Most of them have a workforce of less than 5 people who work mostly 4 hours per day. The division system of labor is based on individual expertise with the dominance of technological development to maintain work effectiveness. The recommendation is to develop human resource management through a planned division of labor to improve the quality of workers and agricultural income